(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This article explores the various linguistic and non-linguistic challenges that translators face when transferring meaning from one language to another. It categorizes these challenges into two main groups: linguistic problems, which arise due to differences in grammar, syntax, and vocabulary between languages, and non-linguistic problems, which encompass cultural, contextual, and ethical considerations. The article emphasizes that translation is not merely a technical task but an art that requires deep cultural awareness and creative problem-solving. Solutions such as localization, consultation with experts, and back translation are highlighted as essential tools for overcoming these challenges. Ultimately, the article underscores the importance of translation in fostering cross-cultural communication and understanding, noting the complexity of the translator’s role in bridging linguistic and cultural gaps.